Targeting Ubiquitin-Specific Protease 7 (USP7) in Cancer: A New Insight to Overcome Drug Resistance - Lu, Jiabin; Zhao, He; Yu, Caini; Kang, Yuanyuan; Yang, Xiaochun (Frontiers in Pharmacology, 2021)
Chemoresistance is one of the leading causes for the failure of tumor treatment. Hence, it is necessary to study further and understand the potential mechanisms of tumor resistance to design and develop novel anti-tumor drugs. Post-translational modifications are critical for proteins’ function under physiological and pathological conditions, among which ubiquitination is the most common one. The protein degradation process mediated by the ubiquitin-proteasome system is the most well-known function of ubiquitination modification. However, ubiquitination also participates in the regulation of many other biological processes, such as protein trafficking and protein-protein interaction. A group of proteins named deubiquitinases can hydrolyze the isopeptide bond and disassemble the ubiquitin-protein conjugates, thus preventing substrate proteins form degradation or other outcomes. Ubiquitin-specific protease 7 (USP7) is one of the most extensively studied deubiquitinases. USP7 exhibits a high expression signature in various malignant tumors, and increased USP7 expression often indicates the poor tumor prognosis, suggesting that USP7 is a marker of tumor prognosis and a potential drug target for anti-tumor therapy. In this review, we first discussed the structure and function of USP7. Further, we summarized the underlying mechanisms by which tumor cells develop resistance to anti-tumor therapies, provided theoretical support for targeting USP7 to overcome drug resistance, and some inspiration for the design and development of USP7 inhibitors.